Glutamatergic and neurometabolic alterations in chronic cocaine users measured with 1H‐magnetic resonance spectroscopy. (30th December 2014) - Hulka, Lea M.; Scheidegger, Milan; Vonmoos, Matthias; Preller, Katrin H.; Baumgartner, Markus R.; Herdener, Marcus; Seifritz, Erich; Henning, Anke; Quednow, Boris B.
Abstract: Cocaine addiction is a chronically relapsing disorder that is associated with harmful consequences. Relapses occur frequently and effective pharmacotherapies are currently sparse. Preclinical studies suggest that altered glutamatergic signaling is crucial for the maintenance of cocaine self‐administration. However, the translational validity of these models is currently unknown. Therefore, we investigated potential differences of glutamate, glutamine and further metabolite levels in the pregenual anterior cingulate cortex (pgACC) and the right dorsolateral prefrontal cortex (rDLPFC) of chronic cocaine users and controls using the PRior knOwledge FITting 2.0 tool in combination with two‐dimensional J‐resolved single‐voxel 1 H‐magnetic resonance spectroscopy at 3T and voxel tissue composition and relaxation correction. Glutamate and glutamine levels did not differ between cocaine users and controls, but higher weekly cocaine use and higher cocaine hair concentrations were associated with lower glutamine/creatine ratios in the pgACC. Interestingly, cocaine users exhibited higher glucose/total creatine ratios than controls in the pgACC and higher choline/creatine ratios in the pgACC and rDLPFC. These results imply that cocaine use is associated with altered cortical glucose metabolism and membrane turnover. Finally, cocaine use over the past 6 months appears to decrease cortical glutamine levels indicating changes in glutamate cycling. Abstract : Glutamate and glutamine levels in the pgACC and the rDLPFC measured with 1 H‐MRS did not differ between cocaine users and controls but higher weekly cocaine use and cocaine hair concentrations were associated with lower glutamine/creatine in the pgACC. Cocaine users exhibited higher glucose/creatine than controls in the pgACC and higher choline/creatine in the pgACC and rDLPFC. Thus, cocaine use is associated with altered glucose metabolism and membrane turnover and appears to decrease glutamine levels indicating changes in glutamate cycling.